KELAYAKAN PENGGUNAAN PENDINGIN THERMOELEKTRIK UNTUK PENGHEMATAN DAYA LISTRIK PADA BASE TRANSCEIVER - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
Thermoelectrically technology is a technology of solid material that can be used as an alternative cooling technology besides cooling system that uses vapor compression that still uses freon. This study aims to determine the feasibility of using thermoelectrically cooling implementation in the indoor BTS (Base Transceiver Station). The use of this thermoelectrically Cooling is to maintain the ideal temperature of the battery by 25 degrees Celsius (250C) which is an ideal temperature. Research is done by testing thermoelectrically by mounting the cooling thermoelectrically in the existing battery cabinets installed in active condition. Ambient temperature measurement is done by using a measuring instrument that has been calibrated.